2016
DOI: 10.1161/circoutcomes.116.002797
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Heart Failure Using Electronic Health Records

Abstract: Background Using electronic health records (EHR) data to predict events and onset of diseases is increasingly common. Relatively little is known, though, about the tradeoffs between data requirements and model utility. Methods and Results We examined the performance of machine learning models trained to detect pre-diagnostic heart failure (HF) in primary care patients using longitudinal EHR data. Model performance was assessed in relation to data requirements defined by: the prediction window length (time be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(37 citation statements)
references
References 13 publications
0
36
1
Order By: Relevance
“…Based on electronic health record data in the primary care setting, these models included information on demographics, vital signs, diagnoses, medications, laboratory values, Framingham heart failure signs and symptoms, hospitalizations, and imaging. Although taking a large number of features into account, the best‐performing model had a receiver operating characteristic area under the curve of about 0.80 19. In the present study, a simple model including only 4 features (of which leg bioimpedance was one) provided slightly higher discriminatory capacity for incident heart failure, which highlights the strong predictive value of the variables included.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Based on electronic health record data in the primary care setting, these models included information on demographics, vital signs, diagnoses, medications, laboratory values, Framingham heart failure signs and symptoms, hospitalizations, and imaging. Although taking a large number of features into account, the best‐performing model had a receiver operating characteristic area under the curve of about 0.80 19. In the present study, a simple model including only 4 features (of which leg bioimpedance was one) provided slightly higher discriminatory capacity for incident heart failure, which highlights the strong predictive value of the variables included.…”
Section: Discussionmentioning
confidence: 56%
“…Machine learning has been employed before in the heart failure setting, but with the primary goal to develop machine learning–based prediction models18, 19 in contrast to the present study, where we proceeded with standard Cox proportional hazards models after the top features had been identified. In a recent study, machine learning algorithms (random forests, gradient boosting machine, and support vector machine) were compared with standard regression models (logistic regression, and Poisson regression) to detect readmission of patients with established heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work on machine learning for early detection of disease has shown that inpatient encounters have been strongly predictive of early mortality. [5] While the SEER database does not include such features, a study could be performed from electronic health records (EHRs) as a data source.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, machine learning has shown to have strong potential for early detection of clinical endpoints in applications such as disease prediction [5][6][7][8] , readmission prediction [9][10][11] , drug adverse event prediction [12] , among others.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal size of a training set to develop automated methods for detecting heart failure has been estimated to be 4000 patients. 109 …”
Section: Using Machine Learning and Decision Supportmentioning
confidence: 99%